Pranayama-an alternative supportive therapy against oxidative stress in essential hypertension - Agarwal, B. K.; Saxena, Tripti; Naz, Sabiha (International Journal of Advances in Medicine, 2017)
Background: Essential hypertension is one of the most prevalent diseases of the world. The underlying pathophysiological abnormalities that lead to the development of the elevated arterial pressure in this disorder remain elusive. Pranayam (yogic breathing exercises) techniques are beneficial in treating a range of stress related disorders such as hypertension and reducing signs of oxidative stress. The present study was undertaken to check effect of Pranayam on oxidative stress in cases of essential hypertension before and after Pranayam. Methods: Total 100 hypertensive subjects and 100 sex matched controls were enrolled in this study. Inclusion criteria include patients with blood pressure ≥ 140/90 mm of Hg, while patients with secondary hypertension, stroke, CAD, MI and diabetes mellitus were excluded. Serum PON-1 was estimated spectrophotometrically by Charlton Menys.V method. Serum SOD estimated spectrophotometrically by Mishra H.P. & Fridovich I,1972 method and Plasma MDA by colorimetric method of Satoch K.et al. We estimated PON-1, SOD and MDA in hypertensive and controls, then we suggested hypertensive for 3 months Pranayam, again the same parameters were measured and compared by using Students T test and one way ANOVA to determine significant differences. Results: Before Pranayam, PON-1 activity was decreased significantly (<0.001) in hypertensive subjects compared to controls. SOD was also decreased significantly (p<0.001) in hypertensives compared to controls and MDA was increased significantly (p<0.001) in hypertensives compared to controls, But after 3 months Pranayam, there was significant (p<0.001) improvement in PON-1 and SOD activity in hypertensives and significant (p<0.001) decrease in MDA levels in hypertensives compared to hypertensives before Pranayam. Conclusions: It is concluded that Pranayam can significantly reduce oxidative stress i.e. generation of free radicals, lipid peroxidation products (MDA) and significant increase in the level of antioxidant enzymes i.e. SOD & PON-1.MDA is a marker of oxidative stress. Pranayam not only reduces oxidative stress but also improves antioxidant status of the individual.